Digitalization in the Accounting and Auditing Profession through ERP Systems - Bogdan-Stefan IONESCU (Chamber of Financial Auditors of Romania, 2021)
The objective of this paper is to observe the possibility of digitizing the accounting and auditing profession by implementing ERP systems, as a result of massive changes in technology over time. The purpose of this paper is to add value to the literature, given the positive or negative aspects of the digitization of the accounting and auditing profession using information systems such as ERP. ERP systems such as information systems have a key role in managing and conducting accounting and auditing, providing support to professional accountants and auditors. The research method used to identify the possibility of digitizing the accounting and auditing profession through ERP information systems is based on the analysis of the archive (literature review), collecting data and information from selected articles from different databases. Following the study, the authors concluded that the accounting and auditing profession can be digitized through the use of ERP information systems, as it allows the automation of a large number of tasks, and the information processed with these systems is much more transparent and accurate.